Validity and Reliability of an Inertial Sensor-Based Knee Proprioception Test in Younger vs. Older Adults - Rahlf, Anna Lina; Petersen, Evi; Rehwinkel, Dominique; Zech, Astrid; Hamacher, Daniel (Frontiers in Sports and Active Living, 2019)
Diminishing proprioception caused by aging effects is associated with a higher risk to fall. However, existing measurement systems of proprioception are often expensive, time-consuming or insufficient regarding reliability evaluation. Inertial sensor-based systems could address these issues. Consequently, this study sought to develop and evaluate an inertial sensor-based joint position sense test. Thereto, intra-session and inter-day test-retest reliability were investigated in a cross-over design. Twenty healthy younger (age: 22±3 years) and 20 healthy older adults (age: 65±5 years) participated in the study. We calculated the mean of the absolute error, the signed error, and the standard deviation of the signed error. Test-retest reliability was quantified by using the intraclass correlation coefficient as well as the bias and limits of agreement. To evaluate the possibility of capturing aging effects, and correspondingly a validation of the system, we calculated Cohen’s d. For the intra-session reliability, fair to good agreements were achieved for the absolute and relative error in all target ranges. Compared to younger adults, we registered a declined joint position sense in older adults with high effects observed for the absolute error in a target range of 15-25 and 55-65 degrees as well as for the variable error in the target ranges of 35-45 and 55-65 degrees. We suggest that inertial sensor-based joint position sense tests are reliable and capable to measure aging effects on proprioception, and are therefore a low-cost and mobile alternative to existing methods.